ANALISIS KETERLAMBATAN PROYEK SERTA DAMPAKNYA TERHADAP BIAYA DAN WAKTU PELAKSANAAN PROYEK - Fitri Nur Kharina; Kusno Adi Sambowo (Jurnal Infrastruktur, 2019)
Construction projects in all regions continues to be developed for the creation of facilities that can be utilized by the community. One of them is the construction of apartments which are now being intensively carried out to meet residential needs for the community. Making a construction project plan always refers to estimates that exist at the time development plan is made, therefore problems can arise if there is a discrepancy between the plans that have been made and the actual reality. So the impact that often occurs is the delay in the time of project implementation which can also be accompanied by an increase in the cost of implementing the project. In the construction project of Cinere Terrace Suites Apartemen & Citywalk, Jakarta there was a delay resulting in a late payment of monthly bill progress by the owner. Based on the above reasons, this research was conducted to find out how the project performance was seen from the cost and time period of the review period. how is the estimated cost and time to complete the overall project work. The method used in the analysis of this study is the Earned Value Method. Based on the results of the analysis carried out for 29 weeks the project performance on schedule has been delayed and cost shows a positive value. For the estimated completion time of the project there is an increase in time whose duration increases from the planned 98 weeks or 685 days to 109,624 weeks or 768 days. While the estimated cost of completing the project from the results of the analysis obtained a value of Rp. 270,147,448,569.16 smaller than the planned cost of Rp. 315,272,727,272.73. With the difference VAC of Rp. 45,125,278,703.57 this shows that there are benefits obtained by the contractor.